Revisitando a dicotomia fala/escrita - Fegadolli, Thaísa Alessandra [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work has by main objective revisit the dichotomy speech/writing from the perspective of scholars in the field of linguistics in relation to the communicative and interactional aspects of language. The research is based on the study of traditional dichotomies that classically distinguish between the oral form and the written form of the language. It is noted here the importance of the study of communication and interaction of individuals, as language being the main aspect responsible for the organization of society, and, of course, also being indispensable for the development of human being. This study shows that the distinctive peculiarities between speech and writing are not of the characteristics of a particular procedure, but differences that are necessary due to the specific moment of creation of an utterance or text, because both the oral and the mode writing may have traces of formality/informality; completeness/incompleteness, among other things. In other words, there is not a distinctive feature that is present only in speech or writing. Thus, this research shows that, by the numberless technological advances, the communication between people has gone through changes and crossed barriers. Therefore, it is clear that with the collaboration of the media, the old dichotomies recommended for speech and writing are being overcome and can no longer be treated strictly to any of the modalities

Este trabalho tem por objetivo principal revisitar a dicotomia fala/escrita sob a perspectiva de estudiosos da área da linguística no que tange aos aspectos comunicativos e interacionais da linguagem. A pesquisa é baseada no estudo das tradicionais dicotomias que classicamente fazem distinção entre a modalidade oral e a modalidade escrita da língua. Evidencia-se aqui a importância do estudo sobre comunicação e a interação dos indivíduos, sendo a linguagem o principal aspecto responsável pela organização da sociedade, além, evidentemente, de também ser indispensável para o desenvolvimento do próprio ser humano. Salienta-se com este estudo que entre fala e escrita existem peculiaridades distintivas não características de uma das modalidades em particular, mas sim diferenças que se fazem necessárias devido ao momento específico de enunciação ou criação de um texto, pois, tanto a modalidade oral quanto a escrita podem apresentar traços de formalidade/informalidade; completude/incompletude; entre outros aspectos. Em outras palavras, não há uma característica distintiva que esteja presente só na fala ou na escrita. Sendo assim, nesta pesquisa mostra-se que, mediante os inúmeros avanços tecnológicos, a interação comunicativa entre as pessoas tem passado por alterações e transposto barreiras. Por isso, verifica-se que, com a colaboração dos meios de comunicação, as dicotomias antigamente preconizadas para fala e escrita estão sendo superadas e já não podem mais ser tratadas de modo estrito a nenhuma das modalidades
Keywords: Fala; Escrita; Linguagem; Comunicação; Tecnologia; Speech; Writing; Language; Interaction; Communication; Technology